2009
DOI: 10.1111/j.1365-2885.2009.01081.x
|View full text |Cite
|
Sign up to set email alerts
|

Transplacental exchange of moxidectin after maternal or fetal intravenous administration in sheep

Abstract: The transplacental exchange of moxidectin after maternal or fetal intravenous (i.v.) administration was studied using the chronically catheterized fetal sheep model. Nine pregnant Suffolk Down sheep of 65.7 +/- 5.9 kg body weight (bw) were surgically prepared to insert polyvinyl catheters in the fetal femoral artery and vein and amniotic sac. The ewes were randomly assigned to two experimental groups. In group 1 (maternal injection) five ewes were treated with an i.v. bolus of 0.2 mg of moxidectin/kg bw. In gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Regarding the sample preparation, most procedures described for MOX residue quantitation in plasma involve clean up steps using solid phase microextraction cartridges (SPME) 8,[11][12][13] and derivatization step. According to literature, the pharmacokinetic (PK) parameters of a veterinary drug vary according to the applied dose, animal species, type of animal and the application site, among others.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the sample preparation, most procedures described for MOX residue quantitation in plasma involve clean up steps using solid phase microextraction cartridges (SPME) 8,[11][12][13] and derivatization step. According to literature, the pharmacokinetic (PK) parameters of a veterinary drug vary according to the applied dose, animal species, type of animal and the application site, among others.…”
Section: Introductionmentioning
confidence: 99%
“…2, 2017 step. [8][9][10][11][12][13] Rarely are described analytical methods by using mass spectrometry as a detector for MOX.14 However, it is important to emphasize that analytical methods based on liquid chromatography coupled to mass spectrometry (HPLC-MS) are sufficiently sensitive and selective to quantify the compounds in very low amounts, not being necessary a derivatization step.Regarding the sample preparation, most procedures described for MOX residue quantitation in plasma involve clean up steps using solid phase microextraction cartridges (SPME) 8,11-13 and derivatization step. According to literature, the pharmacokinetic (PK) parameters of a veterinary drug vary according to the applied dose, animal species, type of animal and the application site, among others.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When combining this knowledge with the fact that these enzymes can be increased in the maternal and fetal livers as well as the placenta (Tracy et al ., ), the values of the reduced elimination half‐life observed in pregnant sheep of the current study could be due to a higher level of metabolism compared to those observed in adult nonpregnant sheep. Consequently, three unidentified metabolites of MXD were found in plasma of pregnant sheep, similar to those previously reported in cows (Lanusse et al ., ) and pregnant sheep (Pérez et al ., ). Although these analytes were observed in the plasma of the control group, they were less intense as chromatographic peaks.…”
Section: Discussionmentioning
confidence: 97%
“…Drug‐free plasma samples (1 mL) were fortified with MXD to reach the following final concentrations: 0.1, 0.5, 1.0, 5.0, 10.0, 25.0, and 50.0 ng/mL. Fortified and experimental plasma samples were vortexed vigorously for 30 sec; after 15 min of incubation at room temperature, an SPE procedure was performed according to our previous procedures (Pérez et al ., ). After SPE, the eluate was evaporated to dryness under a gentle stream of nitrogen at 60 °C in a water bath.…”
Section: Methodsmentioning
confidence: 97%